2016
DOI: 10.3390/nu8080485
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status and Supplementation Practices in Elite Irish Athletes: An Update from 2010/2011

Abstract: Vitamin D deficiency is a global health concern that is prevalent in Ireland. The vitamin D status of elite Irish athletes following implementation of a revised supplementation policy in 2010/2011 has not been explored to date. This study aimed to assess the vitamin D status of elite Irish athletes participating in high-profile sports and establish if equatorial travel, supplementation and/or sunbed use predict vitamin D status. Across Ireland, blood samples (n = 92) were obtained from cricketers (n = 28), box… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 37 publications
(48 reference statements)
0
17
0
1
Order By: Relevance
“…Furthermore, Todd et al found that the prevalence of vitamin D deficiency can be resolved by oral supplementation, but muscle function and respiratory function did not improve after that [40,41]. Brännström et al found no significant correlation between these parameters, including jump and sprint performance, and vitamin D levels [42].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Todd et al found that the prevalence of vitamin D deficiency can be resolved by oral supplementation, but muscle function and respiratory function did not improve after that [40,41]. Brännström et al found no significant correlation between these parameters, including jump and sprint performance, and vitamin D levels [42].…”
Section: Discussionmentioning
confidence: 99%
“…A sharp decrease in the prevalence of vitamin D deficiency from 55% in 2014 to 14% in Irish elite athletes was observed in Ireland, also attributed to the use of supplements. (34) In northern Sweden, vitamin D status was assessed in more than 11,000 men and women between 1986 and 2014. The overall mean serum 25(OH)D was 49.8 AE 23.8 nmol/L.…”
Section: Europementioning
confidence: 99%
“…Vitamin D deficiency may contribute to type II muscle fiber atrophy. This phenomenon is mainly observed in the elderly [4,10,22,23].…”
Section: Vitamin D and Skeletal Muscle Functionmentioning
confidence: 99%